Literature Riview: Pengembangan Lembar Kerja Peserta Didik (LKPD) Berbasis PjBL untuk Meningkatkan Pemahaman Konsep dan Motivasi Belajar Siswa - Puput Sri Yuliyanti; Tri Ariani (Mataram University, 2026)
This study aims to analyze the development of Project-Based Learning (PjBL)-based Student Worksheets (LKPD) as a strategy to improve students' conceptual understanding and learning motivation. The analysis was conducted through a literature review of 50 journals selected from a total of 200 reviewed journals taken from Publish or Perish and the Spiece database. The results of the study show that the PjBL model is able to strengthen students' conceptual understanding because they are directly involved in implementing authentic projects, working collaboratively, and trying to find solutions independently. In addition, various studies also show that PjBL contributes to increasing learning motivation, which is reflected in increased interest, enthusiasm, and student activity during the project completion process. The findings from the reviewed literature include the implementation of PjBL in science, mathematics, biology, and chemistry learning. Overall, this study confirms that PjBL-based LKPD is a tool with great potential in helping students understand the material while motivating them to learn actively. Therefore, the development of PjBL-based LKPD is recommended for implementation in current learning.